Analisis Perbandingan Sistem Pendukung Keputusan Pemilihan Guru Terbaik Menggunakan Metode TOPSIS dan WASPAS - Haida Dafitri; Nur Wulan; Hanna Ritonga (JURIKOM (Jurnal Riset Komputer), 2022)
In an effort to improve the quality of education for students as the nation's next generation, competent teachers are neded in providing education to students. The task of the teacher is to educate, teach, guide, direct, train, assess, and evaluate students. Decision support systems in the world of education are seen as important assets to support fluency and accuracy in achieving a goal. SD Negeri No. 101211 Aek Batang Paya does not yet have a decision support system to assist the principal in selecting the best teacher, manual decision making will result in an assessment that is not objective so it is not appropriate. Therefore, the authors designed a decision support system for comparative analysis between the two methods, namely the TOPSIS method and the WASPAS method with specified criteria. These two methods are compared to find out which method is more effective, easy and fast in the calculation process which is expected to help in determining the best teacher